Brief Insights into Cu2O Electrodeposition: Detailed Progressive Voltammetric and Electrogravimetric Analysis of a Copper Lactate System. Issue 4 (5th March 2020) - Mech, K.; Bisztyga-Szklarz, M.; Szaciłowski, K.
Abstract : The alkaline copper(II) lactate system is the most popular system applied in the electrochemical synthesis of Cu2 O films designed for various purposes. The present work describes step by step the mechanism of electrode reactions accompanying the cathodic polarization of the electrode within a potential range from 0 to −1.0 V in copper lactate based electrolyte. Anodic processes related to the oxidation of products formed during cathodic sweep are also analyzed in detail. The performed studies indicate sequence and mechanisms of reduction of species present in the electrolyte, secondary reduction of products of cathodic reactions as well as oxidation of various species formed at the electrode surface.